Foliar epidermal characteristics of the genus plumbago linn (plumbaginaceae) in Nigeria (2000)
The epidermal morphology of adaxial and abaxial leaf surfaces of the two Plumbago species represented in Nigeria were studied using light microscopy. The epidermal cells are polygonal with straight, thin anticlinal walls. Both taxa arc amphistomatic with anisocytic stomata type on both surfaces. P. zeylanica contains larger cells and stomata. The occurrence of crystal sands and chalk glands on the surfaces of the leaves is of generic importance in the family Plumbaginaceae. Epidermal cell size and number, stomatal size, number and index are characters of taxonomic importance sufficient in separating the two taxa even in sterile specimens. A key is presented for the identification of the species.